(untitled) (American Economist: Journal of Economics Finance and Global Policy, 2026)
The article is dedicated to the comprehensive assessment of corporate clients’ creditworthiness in commercial banks in Uzbekistan under conditions of digitalization of the banking sector. The FinTech-Based Corporate Credit Assessment Framework model, based on the integration of banking, fiscal, and infrastructure data into a unified client risk profile, is substantiated, and its architecture, analytical blocks, and practical application opportunities are disclosed.